Inovasi Pembelajaran di SMK Karya Utama Dolok Masihul - Neni Nurhasanah; Oktrigana Wirian; Ayu Ahari; Dawi Nurjannah; Razak Hardinata Hasibuan; Yogi Andrian (Universitas Muhammadiyah Enrekang, 2023)
This study aims to find out how influential innovation is carried out in the learning process in the classroom, this research method uses a qualitative research method, namely by telling information obtained from interviews with resource persons, in addition to research interviews also using several literature review sources by reading several journal and book references. The findings obtained from this study are: (1) innovation is very necessary because it plays an important role in the learning process, (2) in the learning process must be carried out a learning process that is fun with ice breaking techniques etc., (3) communication between the principal and subordinates is very influential on teacher performance, (4) innovation in schools must be done gradually in order to get effective results.